Matching theory and data: Bayesian vector autoregression and dynamic stochastic general equilibrium models - Alexander Kriwoluzky (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
This paper shows how to identify the structural shocks of a Vector Autore-gression (VAR) while at the same time estimating a dynamic stochastic general equilibrium (DSGE) model that is not assumed to replicate the data generating process. It proposes a framework to estimate the parameters of the VAR model and the DSGE model jointly: the VAR model is identified by sign restrictions derived from the DSGE model; the DSGE model is estimated by matching the corresponding impulse response functions.
Keywords: C51; 330; Bayesian model estimation; vector autoregression; identification; VAR-Modell; Dynamisches Gleichgewicht; Bayes-Statistik; Schätztheorie; Theorie